Konsep Pendidikan Anak Menurut Abdullah Nashih Ulwan - Darisman, Dede (Jurnal Penelitian Pendidikan Islam, 2017)
This article discusses about children's education according to Abdullah Nashih Ulwan. The study results show that children's education in Islam according to Abdullah Nashih Ulwan emphasizes the view that children are seen in the context of the whole human life rather than in a narrow sense. In addition, education is not only in the form of action to achieve a certain rank, but rather on the moral character of children with educational methods that exemplified the Prophet.